Identifying the areas where building information modeling software adds value for general contractors working in the State of Colorado - Sheata, Wally, author; Hamzeh, Farook, advisor; Senior, Bolivar, committee member; Ghosh, Sudipto, committee member (Colorado State University. Libraries, 2011)
The purpose of this research is to identify the areas where Building Information Modeling (BIM) software is currently adding value to General Contractors working in the state of Colorado. The scope of this study is limited to the top Local and National General Contractors in the state of Colorado generating over $100 million a year in revenue as reported by McGraw Hill 2009 Top Colorado Contractors. An exploratory study was completed using industry experts as well as academic research to identify areas where BIM adds value to general contractors. The findings indicate that the majority of the sample group is using BIM on their projects to a certain degree, with very little negative value in any category. There were slight differences when comparing the national and local contractors with regards to the area of added value through the use of BIM, but overall they were very consistent. A conclusion was drawn that while these firms are very interested in BIM and want to continue to grow it within their firms, there are still many areas where BIM has yet to be fully utilized to add value within both the national and local companies.
Keywords: software; project management; construction management; BIM; 3D modeling